Ships - Bailey, Donna (Bailey, Donna., 1990)
Traces early maritime history from the Egyptians to Captain Cook, discusses how sails were developed to use the wind, describes clipper ships, steamships, ocean liners, working ships, inland waterways, and canals, and examines safety at sea and the future of ships.